Reviving vessels: Deconstruction of the khachkar in late medieval tombstone imagery - Abrahamian, Levon (ARAMAZD: Armenian Journal of Near Eastern Studies, 2025)
This study explores the symbolic deconstruction of the classical Armenian khachkar within late medieval tombstone imagery, focusing on the migration of core generative motifs – especially the vessel – into new narrative contexts. Drawing on Ara Demirkhanyan’s tripartite, mirror-symmetrical generative scheme, the authors trace how the khachkar’s structural logic – rooted in a central, life-giving origin – persists in figurative tombstones of the 15th–16th centuries. In these compositions, oversized pitchers adorned with rosettes appear not only in ‘eternal feast’ scenes but also in unexpected contexts, where they symbolically replace or echo the khachkar’s generative core. The study argues that these vessels are not decorative anomalies but encoded markers of rebirth, serving a similar function to the vertical khachkar cross. Tombstones thus become deconstructed khachkars, embedding resurrection symbolism across compositional planes. This continuity reveals a deep integration of cosmological and funerary meaning, where khachkar-derived motifs – particularly the symbolic vessel – mediate the passage from death to spiritual regeneration in late medieval Armenian visual culture.